848 Clinical, Biochemical and Etiological Profile of Fulminant Hepatic Failure of Viral Etiology in Children. (October 2012) - Bhat, D; Dhooria, G; Jain, B; Dhillon, B
Abstract : Viral Hepatitis is a major health problem endemic in many parts of the world. Fulminant hepatic failure is a rare condition that occurs in only 1% of patients hospitalised with an acute viral hepatitis. There is a paucity of literature describing spectrum of fulminant hepatic falure in children in India. Objective: To study the clinical, biochemical and etiological profile of fulminant hepatic failure (FHF) of viral etiology in children. Methods: The study was conducted in 30 children aged group between 1–15 years admitted with FHF of proven viral etiology in Dayanand Medical College and Hospital, Ludhiana. A detailed clinical evaluation including history, physical signs, staging of hepatic encephalopathy with relevant investigations and viral markers were entered in a pretested proforma. Results: Twenty nine patients(96.7%) had enterically transmitted hepatitis. Viral markers for HAV alone was positive in 20 patients (66.67%) and in combination were positive in 28 patients (93.3%), HEV in 7 patients (23.3%) and HBV in 5 patients (16.7%). Eight patients had mixed viral infections. The clinical features included fever and jaundice(100%), anorexia (83.3%), vomiting (76.7%), nausea (73.3%). Complications seen were cerebral edema (53.3%), decreased urine output (30%), GI bleeding(16.6%) and septicaemia (16.6%). The overall survival rate of FHF was seen to be 73.3%. Conclusions: HAV was found to be the commonest viral infection causing FHF either alone or in combination with others. Importance of vaccination of children with HepatitisA and HepatitisB vaccine and improvement in sanitation in prevention of FHF cannot be overemphasised.